A modal based reduction technique for wide loose interfaces and application to a turbine stator. (May 2020) - Battiato, G.; Firrone, C.M.
Highlights: The GSI method is used to predict the dynamics of frictionally damped structures. The reduction method is applied by exploiting cyclic symmetry and HBM hypotheses. A proper design of the hook joint might increase the safety margins of a stator vane. Results show good accuracy of the method with a reduction of computational costs. Abstract: Aim of this research is the prediction of the non-linear forced response of a stator bladed disk for aeronautical applications in the presence of friction contacts at the hook joints (casing – vane segment contact). Due to the large extension of the contact interfaces the use of classic node-to-node contact elements based on the Coulomb friction law becomes cumbersome. Although such approach appears convenient for problems involving small contact regions, it is computationally expensive when large contact interfaces with refined meshes are present between components. In this research, a novel modal interface reduction method is combined with a layer of Jenkins contact elements in order to efficiently predict the effects of friction on the non-linear forced response of the stator bladed disk. The wide rail/hook contact regions are therefore suitable for the application of the presented technique. The goodness of the proposed methodology is quantified both in terms of accuracy and time costs savings on the calculation of non-linear forced responses by exploiting cyclic symmetry hypotheses and the Harmonic Balance Method.